Eleições, pesquisas e estratégias de marketing: a campanha eleitoral de Micarla de Sousa em Natal (2008) - Campos, Emmanuel de Sousa (2011)
From the importance that the political science and the social sciences began to give the electoral programs on TV, were examined in that work academic the effects of research in electoral marketing strategies in Gratuitous Timetable of the Electoral Publicity of the marketing year the candidate Micarla de Sousa (PV) in 2008 for the prefecture of Natal. To analyze the marketing strategies of electoral candidate Micarla de Sousa were used three sources of data: the HGPE on the first part, The interview with the coordinator's marketing campaign of Micarla de Sousa, José Ivan and the quantitative research carried out by the Office IBOPE before and during the period of HGPE. In the analysis of electoral programs, was used the qualitative and quantitative approach, taking as objective to verify whether there was some change in marketing strategy in the candidate Micarla HGPE. So the electoral programs that candidate were transcribed and analyzed and then faced with the results of researches electoral IBOPE carried out in the same period. The interview with the coordinator's marketing campaign the candidate Micarla de Sousa brought relevant information on the construction of public image at the time pre-electoral and electoral. In search of IBOPE, socioeconomic variables were regarded assex, age, education and income. With the collection of this data, there was an intersection of information about the voting intentions of Micarla candidate for mayor of Natal and it was checked how his candidacy has increased or decreased within the surveyed segments and how these oscillations marketing strategies directed at the candidate's HGPE for any specific audience. Also, do not forget that the electoral process is influenced by various factors, because this process is dynamic